The association between the diversity of online activities on smartphones and cognitive function among middle-aged and elderly Chinese adults - Qian Chen; Haoqiang Ji; Qingxin Shang (BMC, 2024)
Abstract Background Many studies have shown that using smartphones can improve cognitive function, but no studies have shown the effect of the diversity of online activities on cognitive function. Therefore, this study explores the association between the diversity of online activity on smartphones and cognitive function among middle-aged and elderly Chinese adults. Methods A total of 13,347 Chinese middle-aged and elderly participants were used in the final analysis. Multivariate linear regression models were used to explore the relationships among the frequency of smartphone use, number of online activities, various activities, and cognitive function. Results We found that 2,143 respondents (16.1%) used smartphones, and the top three online activities were watching news (80.3%), posting moments (72.4%), and chatting (68.0%) among all smartphone users to access the internet. After adjusting for all covariates, we found that the increase in the frequency of smartphone use and the number of online activities were correlated with a higher cognitive score. Moreover, some online activities, such as watching news (β:0.5, 95% CI:0.2-0.8), posting moments (β:0.4, 95% CI:0.2-0.7) playing games (β:0.3, 95% CI:0.03-0.6) and making mobile payments (β:0.3, 95% CI:0.1-0.5) were independently associated with good cognitive function. Discussion In the middle-aged and elderly population, smartphone use plays an important role in cognitive function. Considering the increasing prevalence of smartphones among middle-aged and elderly individuals, this study can provide references and insights for health education and in-depth scientific research related to internet usage.